2017
DOI: 10.1155/2017/6190593
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Biofeedback-Based Trunk Stabilization Training Using a Pressure Biofeedback System in Stroke Patients: A Randomized, Single-Blinded Study

Abstract: The purpose of this study was to assess the effects of audiovisual biofeedback-based trunk stabilization training using a pressure biofeedback system (PBS) in stroke patients. Forty-three chronic stroke patients, who had experienced a stroke more than 6 months ago and were able to sit and walk independently, participated in this study. The subjects were randomly allocated to an experimental group (n = 21) or a control group (n = 22). The experimental group participated in audiovisual biofeedback-based trunk st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The prominent literature base that supports this interpretation is a collection of numerous studies that have shown that people with vestibular deficits ( 28 , 32 ) as well as older adults can use real-time SA cues to reduce sway when the stance position, support surface, or visual inputs are modified during standing balance tasks compared to conditions when cues regarding their body motion are not provided ( 27 ) (Figure 2 ). Young healthy adults ( 33 ), people with peripheral neuropathies ( 34 ), people with mild cognitive impairments ( 35 ), and stroke ( 36 ) have likewise shown reductions in postural sway related metrics compared with baseline. Real-time cues to inform modifications to gait have been shown to reduce M/L trunk tilt during paced heel-to-toe walking ( 37 ) and during narrow stance walking ( 38 ) in people with vestibular deficits.…”
Section: Real-time Use Findingsmentioning
confidence: 99%
“…The prominent literature base that supports this interpretation is a collection of numerous studies that have shown that people with vestibular deficits ( 28 , 32 ) as well as older adults can use real-time SA cues to reduce sway when the stance position, support surface, or visual inputs are modified during standing balance tasks compared to conditions when cues regarding their body motion are not provided ( 27 ) (Figure 2 ). Young healthy adults ( 33 ), people with peripheral neuropathies ( 34 ), people with mild cognitive impairments ( 35 ), and stroke ( 36 ) have likewise shown reductions in postural sway related metrics compared with baseline. Real-time cues to inform modifications to gait have been shown to reduce M/L trunk tilt during paced heel-to-toe walking ( 37 ) and during narrow stance walking ( 38 ) in people with vestibular deficits.…”
Section: Real-time Use Findingsmentioning
confidence: 99%
“…The primary contribution of the trunk muscles is to stabilize the spine and trunk. This stabilization is conditional for free and selective movements of the head or extremities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, providing visual and auditory biofeedback improved trunk control by sustaining the exact contractile force of the trunk muscle, allowing them to experience contractions in different environments. While maintaining this condition, task-oriented training, including arm extension movements, was performed, which is deemed to be the reason for improved trunk control [51]. Task-oriented training combined with ADIM could be an effective treatment method for patients with stroke.…”
Section: Discussionmentioning
confidence: 99%